(untitled) (Indonesian Health Justice Review, 2025)
Indonesian migrant workers and their families often face significant challenges in accessing healthcare both abroad and upon their return. This paper explores the health justice issues surrounding healthcare access for Indonesian migrant workers, focusing on the barriers they encounter in foreign countries and upon repatriation. Using qualitative interviews with migrant workers, healthcare professionals, and government officials, as well as analysis of legal frameworks and international agreements, the research highlights the disparities in healthcare access faced by migrant workers in host countries. These include inadequate health insurance coverage, language barriers, and limited access to quality care, particularly in low-wage, informal sectors. The study also investigates the post-return healthcare challenges, including the lack of adequate health services and support for migrants with long-term health issues acquired abroad. The paper argues that achieving health justice for migrant workers requires stronger bilateral agreements between Indonesia and host countries, improvements in the portability of health benefits, and greater investment in post-return health services. Additionally, the study recommends policy reforms that ensure migrant workers have access to comprehensive healthcare both while working abroad and upon their return, emphasizing the need for more inclusive healthcare policies that protect the health rights of Indonesian migrants and their families.